Pengaruh Komposisi Partikel Styrofoam dan Resin Epoksi pada Komposit Peredam Suara - Ary Prastianto, Bima Kusuma; Rubiono, Gatut; Qiram, Ikhwanul (Proklamasi 45 University, 2023)
Styrofoam (Extruded Polystyrene) waste can be used as a soundproofing material. This study aims to determine the effect of the particle composition of Styrofoam and epoxy resin on the performance of soundproofing composites. The composition between Styrofoam particles and epoxy resin is 20:20; 20:30; and 20:50 grams. Sound absorption test using PVC impedance tube 100 cm long, 15 cm diameter, and 5 mm thick. The variation in the placement distance of the composite from the sound source is 25; 50; and 75 cm and was measured using the sound level meter application. This type of test sound uses a single tone in the frequency range of 0-600 Hz which is recorded per 5 seconds. Composite performance analysis is reviewed based on media density, composite morphological characteristics of Image-J software, and sound absorption coefficient values. The results showed that the greater the composition had increased the density value of composite particles accompanied by a decrease in pore area in the composite media which resulted in a sound absorption coefficient of 15.61 dB at a composition of 20:50 with a distance of 25 cm from the sound source.